2013
DOI: 10.31505/rbtcc.v14i3.549
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric characteristics of the Personality Belief Questionnaire – Short Form

Abstract: This study evaluated the psychometric properties of the Brazilian version of the Personality Belief Questionnaire – Short Form (PBQ-SF). A sample of 700 college students answered to the Brazilian version of the PBQ-SF. The results showed good estimates of reliability (Cronbach’s alpha) of the PBQ-SF scales, indicating a significant association between the beliefs of each of the scales. The results of factor analysis of the PBQ-SF were similar to its original version. Overall, the findings provide support for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
0
4
0
6
Order By: Relevance
“…In this sense, pure PDs are extremely rare [35]. Instead, people often show traits, beliefs and strategies associated with different PDs [14]. Thus, it would seem feasible that such overlap may also be present in the cognitive features of PDs measured by PBQ scales.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this sense, pure PDs are extremely rare [35]. Instead, people often show traits, beliefs and strategies associated with different PDs [14]. Thus, it would seem feasible that such overlap may also be present in the cognitive features of PDs measured by PBQ scales.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, although Butler et al [8] found that some PBQ items discriminated patients with borderline PD from patients with other PDs, factor analytic studies failed to identify a specific factor underlying borderline PD-1 A complete structure matrix is available from the first author upon request. related beliefs [10,14]. Therefore, we did not expect that beliefs associated with borderline PD would correspond to any specific factor.…”
Section: Internal Structurementioning
confidence: 90%
See 1 more Smart Citation
“…The fi rst nine of these are listed in the current version of the DSM (DSM-5), while Passive-Aggressive Personality Disorder was moved from an Axis II personality disorder in the DSM-III-R to Appendix B of the DSM-IV-TR ("Criteria Sets and Axes Provided for Further Study"). Research has established that the PBQ can be considered a practical tool for the measurement of dysfunctional beliefs that are related to recognized personality disorders (Jones, Burrell-Hodgon, & Tate, 2007 ;Leite, Lopes, & Lopes, 2012 ), although path coeffi cients are in the medium range, which indicates that personality disorders are not solely determined by beliefs (Arntz, Dreessen, Schouten, & Weertman, 2004 ). Similarly, the MDT Compound Core Beliefs Questionnaire-Short Version (CCBQ-SV, or, as the standard version in use, CCBQ) is a self-report tool to highlight dysfunctional beliefs in the context of personality clusters for further exploration and treatment planning.…”
Section: Ccbq Developmentmentioning
confidence: 99%
“…Os índices de concordância entre as subescalas das duas versões variaram entre 0,75 e 0,89. Utilizando os itens adaptados por Savoia et al (2006), Leite, Lopes, e Lopes (2012), conduziram uma análise fatorial exploratória a partir das respostas de 700 universitários a uma versão reduzida do PBQ, o Personality Belief Questionnaire Short Form -PBQ-SF (Butler, Brow, Beck, & Grishman, 2002). Os resultados indicaram nove fatores com índices de fidedignidade (alfa de Cronbach) entre 0,55 e 0,86.…”
unclassified